2018
DOI: 10.1186/s12863-018-0684-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence characterization of the 5S ribosomal DNA and the internal transcribed spacer (ITS) region in four European Donax species (Bivalvia: Donacidae)

Abstract: BackgroundThe whole repeat unit of 5S rDNA and the internal transcribed spacer (ITS) of four European Donax species were analysed. After amplifying, cloning and sequencing several 5S and ITS units, their basic features and their variation were described. The phylogenetic usefulness of 5S and ITS sequences in the inference of evolutionary relationships among these wedge clams was also investigated.ResultsThe length of the 5S repeat presented little variation among species, except D. trunculus that differed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
0
3
0
1
Order By: Relevance
“…spp., Erythroculter ilishaeformis Bleeker, Populus fremontii S. Watson, etc. [ 36 , 42 , 43 , 44 ]. In the studied Elaeagnaceae species, there was one TATA-like motif in the NTSs of Sh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…spp., Erythroculter ilishaeformis Bleeker, Populus fremontii S. Watson, etc. [ 36 , 42 , 43 , 44 ]. In the studied Elaeagnaceae species, there was one TATA-like motif in the NTSs of Sh.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 , 36 ]. TATATA, TGATATA, and TATTTA occur in the NTSs of different Donax species, TTATAT in Engistomops spp., TTATGTA in H. rhamnoides and most of the other variants [ 25 , 42 , 43 ]. Assessing the functionality of these modified TATA-boxes as regulatory elements (TATA-box is a signal sequence for RNA polymerase II/III [ 45 ]) is difficult, and a lot of in vitro translation experiments are required.…”
Section: Discussionmentioning
confidence: 99%
“…Siendo de mayor importancia, al considerar los criterios de Huang et al (2017), quienes demuestran que las herramientas moleculares como la PCR convencional resultan de gran importancia en el diagnóstico de especies parasitarias como los nematodos, debido a su elevada especificidad y sensibilidad [18], muy útiles en casos donde las similitudes entre los huevos y los estados larvarios de los helmintos entorpecen la identificación entre especies. El presente estudio confirmó que la secuencia de la región del espaciador transcrito interno (ITS-2) del ADN ribosómico (383 pb) de T. canis, es una región muy conservada (Figura 2), tal como había sido planteado en otros estudios donde se describe que la región ITS contiene dos regiones no codificadoras variables que se encuentran dentro de las repeticiones altamente conservadas del ADNr, entre la subunidad pequeña, la región para 5.8S y los genes para ADNr de la subunidad grande [19]. Estudios basados en el ADN para identificar las especies de nematodos, particularmente utilizando fragmentos de la región ITS del ADN ribosomal demuestran la eficacia de las técnicas moleculares en estudios epidemiológicos [20].…”
Section: Identificación Molecularunclassified
“…Moreover, 5S rRNA genes are organized as tandemly repeated DNA with monomers that consist of a conservative 120 bp coding part and a variable non-coding part (NTS) [18,19]. It was revealed that NTSs often show species-specific polymorphisms [20,21]. The authors successfully used such polymorphisms to develop species-specific molecular markers in a range of plants [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%